Minimalist Lifestyle in the View of the Concepts of Zuhud and Qana’ah in the Qur'an - M. Fiqri Widhy Utomo (Lembaga Yasin AlSys, 2025)
Amid the rise of consumerism, the minimalist lifestyle has gained prominence as a contemporary alternative advocating simplicity and meaningful living. This study critically examines minimalism through the lens of two fundamental Islamic ethical concepts: asceticism (zuhud) and contentment (rida), with the Qur’an serving as the normative foundation. Employing a qualitative literature review and tafsir mawdhu'i (thematic exegesis) methodology, the research compares the convergences and divergences between minimalism and these Islamic principles. The analysis reveals that while both minimalism and Islamic asceticism advocate reducing possessions and avoiding waste, they differ fundamentally in philosophy, motivation, and ultimate purpose. Modern minimalism is predominantly anthropocentric, prioritizing individual happiness and worldly freedom, whereas asceticism and contentment are grounded in a theocentric framework aimed at attaining divine pleasure and eternal joy in the hereafter. The study concludes that integrating the values of asceticism and contentment provides a holistic and spiritually transformative paradigm capable of addressing materialism more comprehensively.